Comparison of effects of sugammadex and neostigmine on QTc prolongation in rabbits under general anesthesia - Erbaş,Mesut (2014)
PURPOSE: To compare the effects of sugammadex and neostigmine, used to antagonize the effects of rocuronium, on the QTc interval. METHODS: This study used 10 adult New Zealand white rabbits of 2.5-3.5 kg randomly divided into two groups: sugammadex group (Group S, n:5) and neostigmine group (Group N, n:5). For general anesthesia administering 2 mg/kg iv propofol and 1 mcg/kg iv fentanyl, 0.6 mg/kg iv rocuronium was given. Later to provide reliable airway for all experimental animals V-Gel Rabbit was inserted. The rabbits were manually ventilated by the same anesthetist. After the V-Gel Rabbit was inserted at 2, 5, 10, 20, 25, 27, 30 and 40 minutes measurements were repeated and recorded. At 25 minutes after induction Group N rabbits were given 0.05 mg/kg iv neostigmine + 0.01 mg/kg iv atropine. Group S were administered 2 mg/kg iv sugammadex. RESULTS: Comparing the QTc interval in the rabbits in Group S and Group N, in the 25th, 27th and 30th minute after muscle relaxant antagonist was administered the QTc interval in the neostigmine group rabbits was significantly increased (p<0.05). CONCLUSION: While sugammadex, administered to antagonize the effect of rocuronium, did not significantly affect the QTc interval, neostigmine+atropine proloned the QTc interval.